RELATIVE THERAPEUTIC EFFICACY AND MOLECULAR WEIGHT DISTRIBUTION OF DRY-HEATED AND n-HEPTANE-HEATED PREPARATIONS OF FACTOR VIII - Abramson, S B; Yang, J; Gomperts, E D; Kasper, C K; Fedor, E J (Thrombosis and Haemostasis, 1987)
Recent reports by Kemoff et al. (1985) and Gomperts et al. (1987; a multicentered multinational trial) showed that Factor VIII (Antihemophilic Factor, or AHF) “wet” heat-treated in n-hep-tane (Profilate Heat-TreatedR) presented a lower risk of transmitting non-A, non-B hepatitis and HIV than AHF products heated as lyophilized powders. No direct comparison has been reported, however, of the therapeutic efficacy of these products. We compared recovery and half-life in vivo for Profilate Heat-Treated11 with those of the dry-heated products HT ProfilateR and Koate HTR. Two sets of six subjects with severe hemophilia A were infused with either Profilate Heat-TreatedR or a dry-heated AHF in a crossover trial, and blood samples were drawn at times from 10 min to 24 hr. Half-life was determined from a linear regression plot of log (plasma AHF) vs. time from 1 hr to 24 hr. The table gives the mean ± one standard deviation of initial recovery and half-life for each product comparison. Unpaired t-tests showed no significant differences between products. Spearman’s rank analysis showed a high degree of correlation for both the initial recovery and half-life of each product pair.Analysis of molecular weight (MW) distributions of Factor VIII:C polypeptides in several commercial products using the method of Weinstein showed the majority of AHF in all products tested to have MW = 100,000 - 110,000. H.T. FactorateR, which exhibited a substantial amount of the AHF polypeptide whose MW approximates 210,000, is reported by the manufacturer to have a half-life = 11 ± 3.9 hr. We thus conclude that the 210,000 MW form of AHF is not required for therapeutic efficacy.